The cost of being an omnivore: mandible wear from plant feeding in a true bug. - Roitberg, B; Gillespie, DR; Quiring, D; Alma, C; Jenner, W; Perry, J; Peterson, J; Salomon, M; VanLaerhoven, S (2005)
Evolutionary and ecological transitions from carnivorous to omnivorous feeding may be constrained by the ability of the animal to cope with disparate types of foods, even if preadaptations for such behaviour exist. The omnivorous true bug, Dicyphus hesperus (Hemiptera: Miridae) requires both animals (small, soft-bodied insects) and plants in its diet and obtains the majority of its dietary and metabolic water from plant feeding. Serrations on the lateral margins of the mandibular stylets wear with age, and this wear is exacerbated when the insects feed on plants compared to those provided free water and no plants. D. hesperus that feed on plants attack fewer prey but consumed similar amounts of prey tissue compared to individuals that were provided free water. Although others have shown mandible wear for plant-chewing animals we show for the first time that plant feeding can impose similar wear on plant-piercing animals as well.